Immunological Markers in Children with Genetic Disorders and Recurrent Respiratory Tract Infections - Kholoussi, Shams; Kholoussi, Naglaa; El Nady, Hala; Ashaat, Engy A.; Abdelkawy, Rania Fawzy Mahmoud; Abo-Shanab, Asem Metwally (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Recurrent respiratory tract infections (RRI) are one of the extremely high common reasons for pediatric visits and hospitalization. Immunodeficiencies are considered as important conditions that may increase the probability of occurrence of RRI. Mannose-binding lectin (MBL2) is a protein of the innate immune system involved in the opsonization and the complement activation. MBL2 deficiency is associated with infectious diseases mainly chest infections; however, subnormal MBL2 levels are also seen in healthy subjects. Primary immunedeficiencies are associated with recurrent infections which mainly appear in early childhood. AIM: The aim of the study was to estimate T and B and natural killer cells percentage and to investigate the MBL2 and immunoglobulins (Igs) serum levels in children with recurrent RRIs in different genetic disorders compared to normal control. METHODS: This study included 50 children having a history of recurrent RRIs. All patients had genetic disorders and referred to National Research Centre for follow-up, in addition to, 25 children, age- and sex-matched as a healthy control group. They were subjected to full clinical examination and laboratory investigations including complete blood count (CBC), CD3, CD4, CD8, CD16, and CD19 by flow cytometry, MBL2 by enzyme-linked immunosorbent assay (ELISA), and Igs serum concentrations by nephelometry. RESULTS: CD16 showed a non-statistical significant difference between both patient groups. Serum levels of IgA in patient groups showed a significant decrease compared to the control group. Moreover, the serum level of IgM results shows a highly significant decrease when compared with the control group. There was no statistically significant difference in MBL2 and IgG serum levels between patient groups and control group. CONCLUSION: Children with genetic disorders and recurrent RRIs showed a statistically significant decrease of IgA and IgM serum levels as compared to the control group, while the serum level of MBL2 did not show significant results.